Policies and instruments affecting water use for bioenergy production - Moraes, Marcia; Ringler, Claudia; Cai, Ximing (Wiley, 2011)
Bioenergy‐related water use can intensify existing water stress, increasing the importance of sustainable management of water resources for sustainable bioenergy production and use. This paper presents a review of policies and instruments that can influence how bioenergy production affects water availability and use. It discusses policies and instruments of importance for water use for bioenergy production, considering both biomass production and the subsequent conversion to solid/liquid/gaseous fuels and electricity. Water policies on the biomass production side should focus on ensuring efficient water use. While environmental policy instruments, such as command‐and‐control approaches, support maintaining specific water quantities and quality standards for biofuel production, market‐based tools can help users identify least‐cost options and increase efficiency. For the energy conversion side, water quality is the key issue that needs to be addressed with adequate policy instruments, but water scarcity can also constrain biofuel industry growth. It is important that policies and instruments for water management on the biomass production and energy conversion side are coordinated to ensure that efficiency is achieved along the entire production chain. Finally, the evaluation of water‐use policies and instruments for bioenergy production should not only relate to their direct impacts on water use, but should also take into account overall impacts on the economy. This is of particular importance given the likely future large‐scale expansion, the potentially large impacts on both water and land, and the potentially large benefits for rural economies of bioenergy expansion. © 2011 Society of Chemical Industry and John Wiley & Sons, Ltd